Weather Derivatives as A Risk Management Tool for Beverages Manufacturers and Breweries in The UK - Ray, Chiranjib (2005)
The weather has an enormous impact on the cash flow of a company. Weather risk has serious implications for a plethora of industries ranging from energy producers, agro industries, beverages producers to ski resorts and golf courses. According to US Department of Commerce, $1 trillion of their economy is sensitive to weather. An estimated 70 per cent of all businesses are affected by weather that extends across geographic and market borders.